PENGARUH PENDEKATAN BERMAIN TERHADAP HASIL SHOOTING BOLA BASKET SISWA XI IPS2 SMAN 1 SUNGAI RAYA - Juliansah, Andi; Supriatna, Eka; Yunitaningrum, Wiwik (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstract: The problem in this is how the effect penelititan approach to playingthe basketball shooting results IPS2 XI students of SMAN 1 Sungai Raya. Thepurpose of this study was to determine the effect on the results of the approachplay basketball shooting IPS2 XI students of SMAN 1 Sungai Raya. The methodin this study is the method of experiment with the form of pre-experimentaldesign. The population in this study a class XI student of SMAN 1 Sungai Rayaamounted to 113 people. Engineering samples using purposive sampling with asample size of 30 people. Analysis of data by t-test analysis. The results of theanalysis of data obtained from the t-test value = 6.748 is greater than the value oftable = 2,045, meaning that the hypothesis is accepted and it can be concluded thatthere are significant approach to playing the basketball shooting results IPS2 XIstudents of SMAN 1 Sungai Raya significant.Keywords: Approach play, Basketball Shooting ResultsAbstrak: Permasalahan dalam penelititan ini adalah bagaimana pengaruhpendekatan bermain terhadap hasil shooting bola basket siswa XI IPS2 SMAN 1Sungai Raya. Tujuan dari penelitian ini adalah untuk mengetahui pengaruhpendekatan bermain terhadap hasil shooting bola basket siswa XI IPS2 SMAN 1Sungai Raya. Metode dalam penelitian ini adalah metode eksperiment denganbentuk pre-eksperimental design. Populasi dalam penelitian ini siswa kelas XISMAN 1 Sungai Raya berjumlah 113 orang. Teknik sampel menggunakansampling purposive dengan jumlah sampel 30 orang. Analisis data dengan analisiuji-t. Hasil analisis data diperoleh nilai dari ttest = 6,748 lebih besar dari nilai ttabel= 2.045, artinya hipotesis diterima dan dapat disimpulkan bahwa terdapatpengaruh pendekatan bermain terhadap hasil shooting bola basket siswa XI IPS2SMAN 1 Sungai Raya yang signifikan.Kata Kunci: Pendekatan bermain, Hasil Shooting Bola Basket